Exploring teachers’ and community’s strategies of empowering pupils on the importance of educational advancement: A case study of Mabvuku-Tafara educational cluster in Epworth, Mabvuku-Tafara District in Harare Metropolitan Province. - Nyahuye, Faith (Midlands State University, 2017)
The purpose of this study was to explore teachers’ and community’s strategies of empowering pupils on the importance of educational advancement. Data was collected in Mabvuku-Tafara educational cluster in Epworth, Mabvuku-Tafara district in Harare Metropolitan province. The researcher employed a qualitative research design. Data was gathered through the use of questionnaires from teachers, interviews for School Heads and drop outs and the focus group discussion for pupils. The target population were students, School drop outs, School Heads and teachers. Stratified random sampling was used to select teachers and students. School Heads and drop outs were purposively selected. The sample selected was made up of 44 subjects comprising 4 School Heads, 16 teachers, 16 students and 8 school drop outs. The results revealed that rate of girls are higher than boys who drop out of school in the Mabvuku- Tafara community. Teachers mostly help who bring educational capital to school and are from affluent homes on the expense of those from disadvantaged homes. The teachers mostly use the traditional methods such as prompt marking and giving of home work to enhance educational advancement. These methods only benefit those children who come from homes where there are books already as well as gadgets such as televisions, computers and the internet. The strategies to empower pupils for educational advancement currently used by teachers of Mabvuku- Tafara cluster only benefit children from homes who already have a reading culture. The country’s economic meltdown, socioeconomic factors and family displacements fuelled the low advancement in schools. The recommendations were that schools in Mabvuku- Tafara education cluster should hold career guidance and awareness campaigns targeting both school pupils and local parents. These should focus on the importance of educational advancement. Community mentors are needed for all children in senior classes to help them realise the importance educational advancement and to build their characters. The School Heads should organise workshops on gender responsive and inclusive teaching methods and multi- cultural approach to teaching. This will curb the problems of discrimination during the teaching and learning process which negatively affects the children from disadvantaged homes. Researches could be carried out by other teachers digging deeper into causes of low advancement in the cluster so as to nip the vice on the bud and disseminating information even to other teachers and school authorities.